Chimeric antigen receptor T-cell therapy for aggressive B-cell lymphomas - Hu, Bei; Korsos, Victoria; Palomba, M. Lia (Frontiers in Oncology, 2024)
Chimeric antigen receptor (CAR) T-cell therapy is a revolutionary approach in the treatment of lymphoma. This review article provides an overview of the four FDA-approved CAR T-cell products for aggressive B-cell lymphoma, including diffuse large B-cell lymphoma and mantle cell lymphoma, highlighting their efficacy and toxicity as well as discussing future directions.